Designing a Model for Bi-criteria Objective Scheduling at Flexible Flowshop Production in Finishing Furniture Industries - Bahaudin, Achmad Fawwaz; Susanty, Aries; Saptadi, Singgih (Diponegoro University, 2025)
The bi-criteria objective scheduling is essential in the Jepara furniture industry due to its competitiveness. Scheduling that not only considers the company's profits but also takes into account the customer's perspective can add significant value to the company. Based on that, this paper proposed a mathematical model for the furniture finishing industry. Then it transformed into a Microsoft Excel Solver model. Cost calculation is also considered to choose the best model. The system's characteristic is flexible flow shop production, not identical at the last stage, and sequence-dependent set up time. The objective of scheduling is to minimize total maximum completion time and total weighted tardiness. There are 3 scenarios in this paper, company focused, customer, and bi-criteria objective. After running the model, scenario 3 is the best choice for completing priority orders on time, while scenario 1 is ideal when seeking efficiency in production with delays being less of a concern.